El modelo B-learning para el fortalecimiento de la comprensión lectora en estudiantes de secundaria. Revisión bibliográfica (Memorias Sifored - Encuentros Educación UAN, 2023)
This bibliographic review aims to know the impact of the B-learning model in strengthening reading comprehension in Spanish in secondary school students. Methodology: a bibliographic review was carried out from a search of documents through Google Scholar, the Scielo database, Redalyc, Scopus, Dialnet and the academic networks, ResearchGate and Academia. Results:17 research articles and 3 master's theses published in the period from 2019 to 2023 are analyzed, with 25% of the documents in English and the remaining 75% in Spanish. Methodological aspects such as the population under study, instruments used in research and the approach of the B-learning model are identified, which influence the strengthening of reading comprehension. Conclusions: it is evident that the implementation of the B-learning model has a positive impact on the processes of reading comprehension, since it is an innovative and flexible model, but there are also factors that affect the development of this modality, such as: the resources and technological tools used in the classroom.
Keywords: Educational innovation; B-learning; reading comprehension; motivation